Subcellular Localization and Assembly Process of the Nisin Biosynthesis Machinery in Lactococcus lactis - Jingqi Chen (American Society for Microbiology, 2020)
ABSTRACT Nisin, a class I lantibiotic, is synthesized as a precursor peptide by a putative membrane-associated lanthionine synthetase complex consisting of the dehydratase NisB, the cyclase NisC, and the ABC transporter NisT. Here, we characterize the subcellular localization and the assembly process of the nisin biosynthesis machinery in Lactococcus lactis by mutational analyses and fluorescence microscopy. Precursor nisin, NisB, and NisC were found to be mainly localized at the cell poles, with a preference for the old poles. They were found to be colocalized at the same spots in these old pole regions, functioning as a nisin modification complex. In contrast, the transporter NisT was found to be distributed uniformly and circumferentially in the membrane. When nisin secretion was blocked by mutagenesis of NisT, the nisin biosynthesis machinery was also visualized directly at a polar position using fluorescence microscopy. The interactions between NisB and other components of the machinery were further studied in vivo, and therefore, the “order of assembly” of the complex was revealed, indicating that NisB directly or indirectly plays the role of a polar “recruiter” in the initial assembly process. Additionally, a potential domain that is located at the surface of the elimination domain of NisB was identified to be crucial for the polar localization of NisB. Based on these data, we propose a model wherein precursor nisin is first completely modified by the nisin biosynthesis machinery, preventing the premature secretion of partially modified peptides, and subsequently secreted by recruited NisT, preferentially at the old pole regions. IMPORTANCE Nisin is the model peptide for LanBC-modified lantibiotics that are commonly modified and exported by a putative synthetase complex. Although the mechanism of maturation, transport, immunity, and regulation is relatively well understood, and structural information is available for some of the proteins involved (B. Li, J. P. J. Yu, J. S. Brunzelle, G. N. Moll, et al., Science 311:1464–1467, 2006, https://doi.org/10.1126/science.1121422; M. A. Ortega, Y. Hao, Q. Zhang, M. C. Walker, et al., Nature 517:509–512, 2015, https://doi.org/10.1038/nature13888; C. Hacker, N. A. Christ, E. Duchardt-Ferner, S. Korn, et al., J Biol Chem 290:28869–28886, 2015, https://doi.org/10.1074/jbc.M115.679969; Y. Y. Xu, X. Li, R. Q. Li, S. S. Li, et al., Acta Crystallogr D Biol Crystallogr 70:1499–1505, 2014, https://doi.org/10.1107/S1399004714004234), the subcellular localization and assembly process of the biosynthesis complex remain to be elucidated. In this study, we determined the spatial distribution of nisin synthesis-related enzymes and the transporter, revealing that the modification and secretion of the precursor nisin mainly occur at the old cell poles of L. lactis and that the transporter NisT is probably recruited later to this spot after the completion of the modification reactions by NisB and NisC. Fluorescently labeled nisin biosynthesis machinery was visualized directly by fluorescence microscopy. To our knowledge, this is the first study to provide direct evidence of the existence of such a complex in vivo. Importantly, the elucidation of the “order of assembly” of the complex will facilitate future endeavors in the investigation of the nisin secretion mechanism and even the isolation and structural characterization of the complete complex.